Qualidade de vida e percepção de estresse dos docentes de uma instituição privada de ensino superior - Letícia de Oliveira Rocha (2024)
Although the teaching profession enjoys great prestige, both from a scientific and social point of view, it is one of the professions most affected by stress, the effects of which compromise the physical and mental health of these professionals, with a direct effect on their quality of life. It is known that stress can affect people of all ages and can also generate impacts on the economic conditions of both employees and employers, as well as the State, with an increase in costs related to human, social and financial resources, given the greater susceptibility to illness. and the inherent risk of occupational absence due to work leave, medical treatment, disability retirement, changes in organizations' management processes and in the worker's private life. Thus, the National Occupational Health Policy and the Health Promotion Policy aim to create means capable of regulating and encouraging the adoption of a work environment that promotes physical, mental, economic and social well-being, reflecting, thus affecting the worker's quality of life. Objective: to evaluate quality of life (QoL) and stress among teachers at a private higher education institution. As secondary objectives, characterize the sociodemographic, health and work-related information among these teachers, as well as identify the relationship between the factors determining a worse quality of life. Methods: This is a cross-sectional, exploratory study with a quantitative approach, whose sample was composed of 119 volunteer teachers from all areas of knowledge from three units belonging to a private higher education institution. The WHOQOL-Bref instruments (to assess QoL), a sociodemographic, occupational and academic training questionnaire were used, in addition to the ESP-10 (to assess stress). After data collection, the information was transferred to Excel and, subsequently, to the Statistical Software for Social Science (SPSS) version 19.0, where we performed the descriptive analysis and calculations of numerical variables. To evaluate the factors associated with a worse quality of life, Pearson's chi-square tests were used in the univariate analysis and the binary logistic regression model in the multivariate analysis. The significance level considered is 5%. All ethical precepts established by Resolution no. 466/12 of the National Health Council will be respected and this study only began after approval by the UFMG Research Ethics Committee. Results: The majority of teachers were female (55.5%), aged between 21 and 64 years old, white (68.9%), with a partner (55.5%) and 64.7% had children. The average salary income was up to 2 minimum wages (43.7%), 55.5% were in the health sciences area and, finally, 47.9% had a master's degree. After multivariate analysis, it was found that the chance of having a worse quality of life was significantly higher for teachers who work up to 6 hours a week, who had poor/regular quality of sleep (OR=3.44; 95% CI 1. 44-8.20) and high stress (OR=2.86; 95% CI 1.10-7.42). Furthermore, teachers with a workload of more than 15 hours had a lower chance of low quality of life (OR=0.26; 95% CI 0.09-0.77) than those with a workload of up to 6 hours. Conclusion: Teachers have an unsatisfactory assessment of their Quality of Life, especially in the environmental domain, with high levels of stress. Furthermore, some factors were determinants of a worse quality of life, including high levels of stress, poor quality of sleep and low weekly working hours. Finally, as a technical product, a technical report will be delivered with the results of this research and publication in a scientific journal related to the topic.